2013
DOI: 10.1001/jamafacial.2013.287
|View full text |Cite
|
Sign up to set email alerts
|

Sternohyoid Flap for Facial Reanimation

Abstract: IMPORTANCE Neuromuscular reanimation of the face provides the correct specific neural functional input and thereby prevents synkinesis. Unfortunately, this ideal situation is rarely encountered in the clinical setting.OBJECTIVES To assess the technical feasibility of and define the surgical procedure for harvesting the sternohyoid muscle as a novel free flap for use in facial reanimation indications.DESIGN, SETTING, AND PARTICIPANTS Fresh, postmortem, nonfixed cadavers were used to define the anatomy and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Second, the strap muscles are grossly more similar to native facial musculature than postural muscles, such as gracilis and serratus anterior, ultimately providing a more naturalappearing smile without adding excess bulk to the face. [12][13] In our case, commissure deviation decreased to 1mm after surgery, which is small enough that it is unlikely to be noticed as asymmetry by the untrained eye. [17][18] Also, the weight of the muscles transferred was 16 g, which is considerably less than that achieved with gracilis, serratus anterior, or latissimus dorsi transfer.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Second, the strap muscles are grossly more similar to native facial musculature than postural muscles, such as gracilis and serratus anterior, ultimately providing a more naturalappearing smile without adding excess bulk to the face. [12][13] In our case, commissure deviation decreased to 1mm after surgery, which is small enough that it is unlikely to be noticed as asymmetry by the untrained eye. [17][18] Also, the weight of the muscles transferred was 16 g, which is considerably less than that achieved with gracilis, serratus anterior, or latissimus dorsi transfer.…”
Section: Discussionmentioning
confidence: 90%
“…Strap muscles have been used for free tissue transfer previously, but not for dual-vector facial reanimation. [12][13][14] The sterno-omohyoid may be a preferable option for many reasons. First, it obviates the need for a separate donor site, especially in patients already undergoing a neck dissection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited case reports of alternate free muscle transfers for facial reanimation have aimed at improving facial contour and bulk. Alam et al 47 first reported the use of a novel sternohyoid muscle free flap using the ansa cervicalis for nerve coaptation and the superior thyroid artery as its vascular pedicle in a series of 24 fresh cadaver flap harvest procedures. Vincent et al 48 later described a dual vector transfer technique using the sternohyoid and omo-hyoid muscles together in cadaveric studies and report good outcomes with one patient who successfully underwent a dual-vector sterno-omohyoid flap with the superior thyroid artery, middle thyroid vein, and ansa cervicalis innervated by the nerve to masseter.…”
Section: Novel Flaps For Dynamic Reanimationmentioning
confidence: 99%